Nano- and Microcarriers as Drug Delivery Systems for Usnic Acid: Review of Literature - Ana Zugic; Vanja Tadic; Snezana Savic (MDPI AG, 2020)
Usnic acid is one of the most investigated lichen secondary metabolites, with several proven biological properties with potential medical relevance. However, its unfavorable physico-chemical properties, as well as observed hepatotoxicity, have discouraged wide-range utilization of usnic acid as a promising therapeutic agent. In accordance with the growing research interest in the development of nanotechnology, especially in the arena of preparations based on natural sources of medicinal compounds, usnic acid incorporated into nano- and microsized colloidal carriers has been a subject of a large number of publications. Therefore, this review discusses the overall results of the studies dealing with usnic acid encapsulated into lipid-based, polymeric and nonorganic micro- and/or nanocarriers, as potential drug delivery systems for this natural compound, in an attempt to introduce its usage as a potential antitumor, antimicrobial, wound-healing, antioxidative and anti-inflammatory drug.